2007
DOI: 10.1037/0735-7028.38.4.421
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of self-administered treatments for depression and anxiety.

Abstract: Self-administered treatments (SATs) are widely used by the general public and mental health professionals. Previous reviews of the efficacy of SATs have included under this category interventions for nonclinical problems, group interventions, and interventions involving significant amounts of therapist contact. The efficacy of SATs for clinical levels of depression and anxiety with minimal therapeutic contact was examined by meta-analyzing 24 studies. The results show large effects for SATs when compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 72 publications
1
22
0
1
Order By: Relevance
“…However, there is no agreed-upon definition of self-help and there is no consensus concerning the appropriate amount of therapist contact for a treatment to be described as "self-help" (Gellatly et al, 2007). Findings have shown that self-help treatments can be effective in treating depression (Gellatly et al, 2007); however, effectiveness can depend, in part, on how serious the patient's depressive symptoms are, because these treatments may be insufficient for patients with more-severe depressive symptoms (Menchola, Arkowitz, and Burke, 2007).…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is no agreed-upon definition of self-help and there is no consensus concerning the appropriate amount of therapist contact for a treatment to be described as "self-help" (Gellatly et al, 2007). Findings have shown that self-help treatments can be effective in treating depression (Gellatly et al, 2007); however, effectiveness can depend, in part, on how serious the patient's depressive symptoms are, because these treatments may be insufficient for patients with more-severe depressive symptoms (Menchola, Arkowitz, and Burke, 2007).…”
Section: Diagnosismentioning
confidence: 99%
“…Self-help treatments, or self-administered treatments, are typically defined as treatments without therapist contact. They usually encompass media-based treatments, such as books, manuals, audiotapes, or some combination (Gellatly et al, 2007;Menchola, Arkowitz, and Burke, 2007). However, there is no agreed-upon definition of self-help and there is no consensus concerning the appropriate amount of therapist contact for a treatment to be described as "self-help" (Gellatly et al, 2007).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…En este sentido, se plantea que problemas más sencillos como las FE podrían requerir una menor guía o contacto del terapeuta, mientras que en problemas más graves el apoyo del clínico podría ser de mayor relevancia (Botella et al, 2010;Menchola, Arkowitz, y Burke, 2007 …”
Section: Introducción Generalunclassified
“…Thus, it is also necessary to consider studies indicating that, whereas self-help interventions without therapist contact can be useful to treat simple psychological disorders (i.e, specific phobias), they may be insufficient for more severe mental disorders [44,82]. Although there is recent evidence showing the utility of selfguided Internet Interventions for severe disorders (i.e., depression) [51], this issue remains unclear.…”
Section: No-fearmentioning
confidence: 99%